2004
DOI: 10.1073/pnas.0400061101
|View full text |Cite
|
Sign up to set email alerts
|

Epitope-specific immunotherapy induces immune deviation of proinflammatory T cells in rheumatoid arthritis

Abstract: Modulation of epitope-specific immune responses would represent a major addition to available therapeutic options for many autoimmune diseases. The objective of this work was to induce immune deviation by mucosal peptide-specific immunotherapy in rheumatoid arthritis (RA) patients, and to dissect the related immunological mechanisms by using a technology for the detection of low-affinity class II-restricted peptide-specific T cells. A group of patients with early RA was treated for 6 months orally with dnaJP1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
157
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 202 publications
(163 citation statements)
references
References 41 publications
3
157
0
3
Order By: Relevance
“…Recently, phase I and phase II immunotherapy trials with epitopes derived from DnaJ HSP and Hsp60 showed great promise in RA (refs. 23 and 43 and Koffeman E, et al: unpublished observations) and type II diabetes mellitus (23,44), respectively. Over the years, a large amount of data has been gathered, in experimental arthritis models as well as in patients with JIA and patients with RA, suggesting that Hsp60 is a potential target for immunotherapy in arthritis (24).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Recently, phase I and phase II immunotherapy trials with epitopes derived from DnaJ HSP and Hsp60 showed great promise in RA (refs. 23 and 43 and Koffeman E, et al: unpublished observations) and type II diabetes mellitus (23,44), respectively. Over the years, a large amount of data has been gathered, in experimental arthritis models as well as in patients with JIA and patients with RA, suggesting that Hsp60 is a potential target for immunotherapy in arthritis (24).…”
Section: Discussionmentioning
confidence: 83%
“…We previously showed that DnaJ P1, a peptide derived from another HSP, induces proinflammatory responses in PBMCs from patients with early RA and can be used to modulate autoimmune inflammation in these patients (23). The results from the present study show that the phenomenon of disease-and inflammation-specific recognition of HSP-derived epitopic peptides, which we first described in patients with RA using DnaJ P1, is, in reality, more complex and involves peptides that are functionally similar to DnaJ P1 (proinflammatory) as well as others that are quite different (50).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7] Studies on human autoimmune diseases including SLE have reported amelioration of inflammatory responses and increases in CD4 þ CD25 þ Treg cells following treatment with self-antigen-derived peptides. [8][9][10][11][12][13][14][15][16] Similarly, self-antigen-derived peptides have also been used to induce immune tolerance and ameliorate disease in murine lupus models. 15,[17][18][19][20][21][22][23][24][25] Our group has developed a novel peptide pConsensus (pCons) that is based on MHC Class I and Class II T-cell determinants in the heavy chain region of murine anti-DNA IgG.…”
Section: Introductionmentioning
confidence: 99%
“…HSP immunisations have been shown to inhibit autoimmune disorders such as diabetes and arthritis both in animal models and in initial clinical trials in patients with chronic inflammatory disease. [5][6][7][8][9][10][11][12] Over the past years, several research groups have shown that HSP reactive T cells might play a role in this regulatory function and in the induction of anti-inflammatory cytokines in chronic inflammation.…”
mentioning
confidence: 99%